ANALISIS KRITIK SOSIAL KEPADA KONTRAKTOR DAN MASYARAKAT DALAM PUISI ESAI “ABORSI DI PALIPPIS” KARYA SYUMAN SAEHA - Naim Irmayani; Andriani Andriani (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This research is motivated by how the social criticism contained in the poetry essay "Abortion in Palippis" by Syuman Saeha. The purpose of this research is to find out the social criticism in Syuman Saeha's essay "Abortion in Palippis". The method used in this study is a qualitative descriptive method to describe data in the form of mental elements and social criticism in the poem essay "Abortion di Palippis". Shuman Saeha's work. The research technique used is document analysis, namely the poetry essay "Abortion di Palippis" by Syuman Saeha and interviewing the resource person, Syuman Saeha, as the poet of the essay "Abortion di Palippis".The research results obtained were the inner elements of the essay poetry "Abortion di Palippis" consisting of theme, taste, tone of atmosphere and message. The social criticism obtained is in the form of criticism against the government, contractors and the community. Social criticism of the government has 4 points, against contractors 3 points and against society 3 points. Of the three targets of criticism, the government is seen as the party most responsible for creating social problems as is the social criticism obtained in the poem Shuman Saeha's "Abortion di Palippis" essay.